2016
DOI: 10.1155/2016/2483163
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Strategies for Oxidative Stress‐Related Cardiovascular Diseases: Removal of Excess Reactive Oxygen Species in Adult Stem Cells

Abstract: Accumulating evidence indicates that acute and chronic uncontrolled overproduction of oxidative stress-related factors including reactive oxygen species (ROS) causes cardiovascular diseases (CVDs), atherosclerosis, and diabetes. Moreover ROS mediate various signaling pathways underlying vascular inflammation in ischemic tissues. With respect to stem cell-based therapy, several studies clearly indicate that modulating antioxidant production at cellular levels enhances stem/progenitor cell functionalities, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 163 publications
(152 reference statements)
0
27
0
Order By: Relevance
“…Oxidative stress is closely associated with endothelial cell injury and AS pathogenesis [25]. Oxidative stress induced by ox-LDL mainly results from excessive ROS generation and decreased activity of anti-oxidative enzymes, such as SOD [26].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is closely associated with endothelial cell injury and AS pathogenesis [25]. Oxidative stress induced by ox-LDL mainly results from excessive ROS generation and decreased activity of anti-oxidative enzymes, such as SOD [26].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, Lisosan G prevents the LPS-induced activation of the NF- κ B signaling. Thus, Lisosan G joins other natural compounds with antioxidant properties being able to improve overall bioactivity of EPCs exposed to inflammatory insults by resetting the crosstalk between several components of the adaptative intracellular network [49]. …”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation is that anti-hyperglycemic drugs may not decrease oxidative stress effectively. Antioxidant therapy has successfully decreased ROS levels, and improved endothelial dysfunction in an animal model and in type 1 diabetic patients [8,15,16]; however, large scale clinical trials have shown disappointing results with classic antioxidants, including vitamin E, vitamin C, and alpha-lipoic acid, failing to reduce the incidence of vascular complications in patients with type 2 diabetes [17,18]. These findings indicate that development of new alternative antioxidant approaches to target vascular ROS is needed.…”
Section: Introductionmentioning
confidence: 99%